2020
DOI: 10.3389/fimmu.2020.00604
|View full text |Cite
|
Sign up to set email alerts
|

The Biogenesis, Biology, and Clinical Significance of Exosomal PD-L1 in Cancer

Abstract: The exosome serves as a trafficking vehicle for transport of programmed death-ligand 1 (PD-L1) into receptor cells. In tumor microenvironment, distant tumor cells can remotely attack activated T cells by exosomal PD-L1. Here, we summerize the biogenesis and transport process of exosomal PD-L1. Then, we focus on the cancer biology of exosomal PD-L1 in immunosuppression and the mechanism by which it inhibits T cells. Finally, we highlight the prospects of exosomal PD-L1 as a tumor biomarker and its significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 87 publications
1
49
1
Order By: Relevance
“…Moreover, there is crosstalk between IFN-γ and epidermal growth factor in the regulation of the distribution of ExoPD-L1 and cellular PD-L1 in breast cancer cells ( Monypenny et al, 2018 ). Recent studies have revealed that both cell-surface PD-L1 and ExoPD-L1 play crucial roles in immunosuppression, tumor progression, and response to cancer immunotherapy ( Zou et al, 2016 ; Chen G. et al, 2018 ; Theodoraki et al, 2018b ; Fan et al, 2019 ; Kim et al, 2019 ; Xie F. et al, 2019 ; Cordonnier et al, 2020 ; Huang et al, 2020 ; Tang et al, 2020 ). Nevertheless, the manner in which inflammatory cytokines affect PD-L1 expression on tumor cells and exosomes is still elusive ( Akbay et al, 2013 ; Chen et al, 2015 , 2019 ; Wang X. et al, 2017 ; Li et al, 2018 ; Lin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is crosstalk between IFN-γ and epidermal growth factor in the regulation of the distribution of ExoPD-L1 and cellular PD-L1 in breast cancer cells ( Monypenny et al, 2018 ). Recent studies have revealed that both cell-surface PD-L1 and ExoPD-L1 play crucial roles in immunosuppression, tumor progression, and response to cancer immunotherapy ( Zou et al, 2016 ; Chen G. et al, 2018 ; Theodoraki et al, 2018b ; Fan et al, 2019 ; Kim et al, 2019 ; Xie F. et al, 2019 ; Cordonnier et al, 2020 ; Huang et al, 2020 ; Tang et al, 2020 ). Nevertheless, the manner in which inflammatory cytokines affect PD-L1 expression on tumor cells and exosomes is still elusive ( Akbay et al, 2013 ; Chen et al, 2015 , 2019 ; Wang X. et al, 2017 ; Li et al, 2018 ; Lin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to provide individualized precise treatment and to predict tumor response to immunotherapy ( Madore et al, 2015 ; Kaunitz et al, 2017 ; Sui et al, 2018 ; Liu and Wu, 2019 ). To fulfill the need for real-time monitoring, the analysis of liquid biopsy-based circulating biomarkers is preferred ( Nishino et al, 2013 ; Ando et al, 2019 ; Gregg et al, 2019 ; Kloten et al, 2019 ; Tang et al, 2020 ). Recent studies demonstrated that melanoma patients who were less responsive to anti-PD-1 blockade had a significantly higher level of circulating ExoPD-L1 prior to treatment as compared with responders ( Chen G. et al, 2018 ).…”
Section: Potential Clinical Implication Of Circulating Exopd-l1 As a mentioning
confidence: 99%
“…Chen et al recently showed that PD-L1 is enriched in exosomes, when compared with that in melanoma microvesicles, suggesting that exosomes are the primary source of PD-L1 among EVs in this cancer type (34). Other studies have confirmed exosomal PD-L1 in melanoma, prostate cancer, breast cancer, glioblastoma, head and neck cancer, lung cancer, and other tumors (35,36). However, the success of immunotherapy depends on the expression profile of these different ICPs.…”
Section: Checkpoint Inhibitor As a Contributor To Liquid Biopsymentioning
confidence: 99%
“…Furthermore, Exos biologically functionalized by controlling source cells and downstream target cells. Self‐governing secretion of nucleic acids, proteins, and diverse cellular metabolites through Exos is vital for the differentiation and maturation of source cells and homeostasis (C. Hu et al, 2020; Y. Tang et al, 2020; Yue et al, 2020). Meanwhile, Exos can transport their genetic materials, such as DNA fragments, mRNAs, miRNAs, and long noncoding RNAs (lncRNAs), into target cells to modulate their genes and proteins expressions and to reinforce the activity of related pathways (Hashemian et al, 2020; Kwon et al, 2020; W. Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%